Pentingnya Asesmen Formatif Dalam Meningkatkan Disiplin Belajar Peserta Didik - Ester Dewi Barek Goran; Yulius Rustan Effendi; Romadhon (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Effective learning requires discipline, yet there has been a decline in students' discipline. Teachers must prioritize formative assessment in the learning process to enhance student success. Implementing this formative assessment makes it easier for teachers to measure students' learning achievements, enabling them to provide feedback for improvement in future learning processes. The aim of this study is threefold: (1) to understand the importance of applying formative assessment in learning; (2) to understand the steps teachers take when applying formative assessment; and (3) to understand the impact of applying formative assessment on students. This study decisively adopts a qualitative research design with a descriptive approach. Data were collected rigorously through interviews, observations, and document studies, ensuring a comprehensive understanding of the subject matter. The results of this study show that formative assessment is important for increasing students' engagement and discipline in learning, as well as helping teachers evaluate the effectiveness of learning during the process. Formative assessment is a powerful tool employed through diverse learning activities that teachers facilitate throughout the educational process. It is vital for enhancing students' learning, as it strengthens their discipline and motivation.